Bruges. Vue sur Notre-Dame - View on Notre-Dame church, GP009180 - Auteur inconnu (Wikimedia Commons)
Carte postale ancienne issue de Wikimedia Commons. Titre: Bruges. Vue sur Notre-Dame - View on Notre-Dame church, GP009180. Title Bruges. Vue sur Notre-Dame - View on Notre-Dame church Date [date de publication inconnue] Publisher Paris: Neurdein Uniform title Brugge. Panorama Series Belgique. Province de Flandre occidentale. Cartes postales Belgium. Province of West Flanders. Postcards België. Provincie West-Vlaanderen. Prentkaarten Genre Post cards Extent 1 kaart / postcard: Graphic Black-and-white. Language French Additional info General note: Panorama met Onze-Lieve-Vrouwkerk General note: Titelgegevens ontleend aan prentkaart Source Library Catalog Source ID lbsn9991129370101471
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale